Colonial legacy and the experience of First Nations women in cervical cancer screening: a Canadian multi-community study. Issue 4 (7th August 2016) - Wakewich, Pamela; Wood, Brianne; Davey, Crystal; Laframboise, Ashlie; Zehbe, Ingeborg; ,
Abstract : Regular Papanicolaou (Pap) screening has dramatically reduced cervical cancer incidence in Canada since the 1950s. However, Indigenous women's rates of cervical cancer remain disproportionately high, a factor which is not acknowledged in national media or in educational materials reporting Canada's new cervical cancer screening guidelines. Here, we present findings from a cervical cancer screening initiative in Northwestern Ontario. Based on participatory action research, we worked with 10 First Nations communities in the Robinson Superior Treaty area to increase awareness of cervical cancer risk, develop culturally sensitive tools for screening and education and test the efficacy of human papillomavirus (HPV) self-sampling as an alternative to Pap cytology. We conducted 16 interviews with health care professionals and 9 focus groups with 69 women from the communities. A central theme for both health care providers (HCPs) and community members was the colonial legacy and its influence on women's experiences of cervical cancer screening. This was evidenced by a strong sense of body shyness, including shame related to sexuality and sexually transmitted infections, concerns about confidentiality in clinical encounters and distrust or caution around HCPs. Reaffirming women's traditional caregiving and educational roles, enhancing mother and daughter communication, improving cultural sensitivity in health care and education and adoption of HPV self-sampling to increase women's privacy and control of the cervical cancer screening experience were endorsed. We argue that education and screening initiatives must reflect the cultural preferences of Indigenous women, empowering them to take control of their experiences of health and body in cervical cancer screening.